Acquisitions through Emerging Market Corporations inside Created Markets: Assessing the impact of Indian M&As on shareholder value and risk in emerging markets (Journal of Advances and Scholarly Researches in Allied Education, 2016)
This paper examines the results of merger and acquisition (M&A) activities of Indian corporates. The key issue is the extent to which these M&As create value for the shareholders of the Indian acquiring firms. There are two components to this question relating to the short and longer term impacts. First, how does the market react to the announcements related M&As by Indian corporates in the short term? And second, how successful are the Indian companies in creating value to the shareholder in the long run? The research further considers the firm specific level using a sample of M&A companies and how media material may have contributed to the market impacts experienced by the corporates. The purpose of this paper is to answer whether a Developed Country firm would generate higher returns to its shareholders by acquiring a company from the India or by acquiring an Emerging Market target. It includes an extensive literature review that covers the main motives and theories behind M&As. Also, the cross border M&A theory and the rationale behind the internationalization and location decisions are discussed. Furthermore, an analysis of empirical studies in Indian Domestic M&A, cross border M&A and M&A in Emerging Markets is presented. Emerging markets have become important investment destination for international investors as they seek opportunities to grow and diversify their investment portfolios. At the same time, emerging markets are perceived to be riskier than developed markets. It is therefore imperative for the international investor to fully comprehend and appreciate the risk faced by their investments in the emerging markets and the drivers of the underlying their value.